Stratospheric Injection of Massive Smoke Plume From Canadian Boreal Fires in 2017 as Seen by DSCOVR‐EPIC, CALIOP, and OMPS‐LP Observations. Issue 10 (18th May 2020) - Torres, O.; Bhartia, P. K.; Taha, G.; Jethva, H.; Das, S.; Colarco, P.; Krotkov, N.; Omar, A.; Ahn, C.
Abstract: A carbonaceous aerosol plume associated with wildfires in British Columbia in August 2017 reached the stratosphere a few days following the fires onset. The Earth Polychromatic Imaging Camera (EPIC) sensor onboard the Deep Space Climate Observatory (DSCOVR) satellite observed the spatial and temporal evolution of the plume for about 6 weeks. EPIC's near‐hourly observations of the Earth's sunlit disk allowed for monitoring the smoke plume several times per day. High ultraviolet aerosol index values pointed to the presence of an aerosol layer in the upper troposphere and lower stratosphere, confirmed with Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) lidar observations. EPIC aerosol optical depth retrievals and CALIOP information on layer height were used to estimate the stratospheric portion of the aerosol mass, reaching a maximum of 268 ± 86 Kt 3 days after the onset of the wildfires. About 10% of this aerosol mass reached the stratosphere on 13 August, whereas the remaining 90% did so over the following 2 days. Observed daytime and inferred nighttime rates of stratospheric aerosol mass increase showed a more rapid daytime increase, consistent with variability in diurnal insolation, suggesting that solar radiation driven processes may have contributed to the observed stratospheric aerosol mass increase. Global modeling results support the possible role of diabatic aerosol self‐lofting. Ozone Mapping and Profiler Suite Limb Profiler (OMPS‐LP) aerosol retrievals showed the spread of stratospheric aerosols in the Northern Hemisphere, reaching peak concentration between October 2017 and January 2018, when about half the Northern Hemisphere experienced a detectable enhancement of stratospheric aerosols with respect to preinjection conditions. The lifetime and aerosol mass of this smoke event were comparable to those of a moderate volcanic eruption. Plain Language Summary: The 2017 wildfire season in western North America was unusually intense. As documented by several media outlets (https://globalnews.ca/news/3921710/b‐c‐year‐in‐review‐2017‐wildfires/ ), over 1, 300 fires and more than 1.2 million hectares burned were reported between April and November in the Canadian British Columbia province. In mid‐August, the combination of very intense boreal fires and typical summer meteorological conditions led to the rapid formation fire‐triggered convective clouds of considerable vertical extent. Because of the pyroconvective activity of these clouds, thousands of tons of carbon‐containing smoke particles, also known as aerosols, were injected above 10 km in a few hours, some of which may have been directly injected in the stratosphere. Heating of the aerosol layer resulting from absorption of solar radiation induced lofting of the smoke plume into the stratosphere (generally above 12 km in this area), a region of the atmosphere where aerosol removal processes are slow. Because of their long residence time, stratospheric aerosols are very important as they affect Earth's radiative budget and climate. In this paper, we use satellite observations and models to describe the extended three‐dimensional spatial distribution and long lifetime of the resulting aerosol plume that made this an unusual aerosol event. Key Points: Carbonaceous aerosols generated by the 2017 Canadian wildfires reached the upper troposphere and lower stratosphere Diabatic heating from aerosol absorption of solar radiation may have triggered the lofting of the aerosol layer from the upper troposphere to the stratosphere The aerosol layer covered the northern hemisphere from about 30°N to the North Pole for a 10‐month period between August 2017 to June 2018